Multiple commitments and behaviors: a mixed concept approach. Issue 2 (18th April 2017) - Hoppe, Daniel
Abstract : Purpose: The purpose of this paper is to investigate the interrelationships between different foci of commitment, namely, department commitment (DC) and corporate brand commitment (CBC), and their relationship toward favorable employee behavior on the same level of aggregation. Design/methodology/approach: A survey at a maximum care hospital in Germany was conducted ( N = 366). Findings: Integrating two contrasting frameworks ("key mediating concept" and "compatibility concept") into a mixed model by using the accessibility-diagnosticity framework, support for the predictive nature of DC on CBC was found. Based on the compatibility principle, relationships between DC and department citizenship behavior (DCB) as well as between CBC and brand citizenship behavior (BCB) are empirically supported. Negligible spillover effects were found. Research limitations/implications: Understanding the relationship between DC and CBC shows new ways to strengthen CBC, as the generation of DC has synergetic effects on favorable employee behaviors. DC facilitates employee behavior supporting the department and has an indirect impact on BCB, which is extremely important in service sectors with limited differentiation potential. Originality/value: This paper provides a new theoretical reasoning to derive relationships between different foci of commitments applicable for future research. Additionally, it is the first implementation of CBC in a multi-foci framework of commitments and favorable employee behaviors. Moreover, it is the first application of the BCB construct in a healthcare context. Finally, empirical support for a mixed concept approach over past models in a multi-foci framework is provided.